An X‐band high‐efficiency GaN load modulated balanced amplifier MMIC. Issue 6 (11th February 2020) - Wang, Guangnian; Tao, Hong‐Qi
Abstract: An X‐band high‐efficiency GaN load modulated balanced amplifier monolithic microwave integrated circuit (MMIC) composed of 90° Lange Couplers at radio frequency (RF) input and output, a pair of balanced power amplifier (BPA) and a control signal (CS) PA is presented in this article. The impedance of the BPA is modulated by varying the amplitude and phase of the injected CS at same frequency. The prototype has a peak continuous wave output power of 42.5 dBm, with efficiency of 45% to 55% at peak power and 40% to 45% at 6 dB output back‐off over 8 to 11 GHz. The average efficiency for the 37.2 dBm output power is 40%, with adjacent channel leakage ratio of −32 dBc without digital predistortion at 10 GHz center frequency.